Molecular Ordering at the Interface Between Liquid Water and Rutile TiO2(110). Issue 17 (1st September 2015) - Serrano, Giulia; Bonanni, Beatrice; Di Giovannantonio, Marco; Kosmala, Tomasz; Schmid, Michael; Diebold, Ulrike; Di Carlo, Aldo; Cheng, Jun; VandeVondele, Joost; Wandelt, Klaus; Goletti, Claudio
Abstract : The pivotal importance of TiO2 as a technological material involves most applications in an aqueous environment, but the single‐crystal TiO2 /bulk‐water interfaces are almost completely unexplored, since up to date solid/liquid interfaces are more difficult to access than surfaces in ultrahigh vacuum (UHV). Only a few techniques (as scanning probe microscopy) offer the opportunity to explore these systems under realistic conditions. The rutile TiO2 (110) surface immersed in high‐purity water is studied by in situ scanning tunneling microscopy. The large‐scale surface morphology as obtained after preparation under UHV conditions remains unchanged upon prolonged exposure to bulk water. Moreover, in contrast to UHV, atomically resolved images show a twofold periodicity along the [001] direction, indicative of an ordered structure resulting from the hydration layer. This is consistent with density‐functional theory based molecular dynamics simulations where neighboring interfacial molecules of the first water layer in contact with the bulk liquid form dimers. By contrast, this dimerization is not observed for a single adsorbed water monolayer, i.e., in the absence of bulk water. Abstract : The rutile TiO2 (110)/liquid water interface is studied by scanning tunneling microscopy, and results are different from the same system studied in ultrahigh vacuum: water molecules form dimers along well defined directions of the surface. Theoretical calculations fully confirm the experimental results. Investigation of TiO2 under realistic conditions is a decisive step for deeply understanding the application of this material.